(untitled) (Heritage, 2025)
The subject of research in this paper are characters of children with disabilities, in selected works included in the school and home reading covered by the teaching and learning syllabi of the Serbian language and literature for elementary school. At the teaching interpretation level, the analysis focuses on the novels Heidi by Johanna Spyri and About the Button and Happiness by Jasminka Petrović. The paper discusses the degree of understanding of the analyzed works among students of different ages, as well as possible ways of their interpretation in contemporary teaching. It highlights significant forms of work prompted by the texts, which further affirm various interpretative, research and creative approaches in teaching. Particular attention is given to exploring literary depictions of disability from the perspective of various theoretical modalities (medical and social approaches), the loneliness of characters with disabilities, their fragility, and fears arising from the social and cultural context of inclusion in the community. The work as a whole delves into the educational domain of teaching literature and points to the importance of fostering empathy in students and raising their awareness of the necessity of providing support and assistance to persons with disabilities.